2023
DOI: 10.1186/s12902-023-01411-5
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride glucose-body mass index and hypertension risk in iranian adults: a population-based study

Abstract: Background Insulin resistance (IR) and obesity are risk factors for hypertension; triglyceride-glucose (TyG) is known as a surrogate for IR. The present study investigated the association between the triglyceride-glucose body mass index (TyG-BMI) index and the risk of hypertension in Iranian adults. Methods This study was conducted on a sample of 8,610 participants from the baseline phase of the Ravansar non- communicable diseases (RaNCD) in Iran. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Accordingly, both logistic regression and decision tree models showed that literacy was a key risk factor for cognitive dysfunction in older adults. The association between a high BMI and an increased risk of cognitive dysfunction in the present study may be because a high BMI tends to be associated with an increased risk of cardiovascular diseases such as hypertension, hyperlipidaemia, and diabetes mellitus [ 19 21 ], and these cardiovascular diseases may have an impact on the mitochondrial network system [ 22 ], which affects cerebrovascular oxygen sensing in the brain and can lead to cognitive decline. In addition, in a state of obesity, adipose tissue secretes a number of inflammatory factors, such as interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-α) [ 23 ], which may cause an inflammatory response in the circulatory system and adversely affect brain function, thereby increasing the risk of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, both logistic regression and decision tree models showed that literacy was a key risk factor for cognitive dysfunction in older adults. The association between a high BMI and an increased risk of cognitive dysfunction in the present study may be because a high BMI tends to be associated with an increased risk of cardiovascular diseases such as hypertension, hyperlipidaemia, and diabetes mellitus [ 19 21 ], and these cardiovascular diseases may have an impact on the mitochondrial network system [ 22 ], which affects cerebrovascular oxygen sensing in the brain and can lead to cognitive decline. In addition, in a state of obesity, adipose tissue secretes a number of inflammatory factors, such as interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-α) [ 23 ], which may cause an inflammatory response in the circulatory system and adversely affect brain function, thereby increasing the risk of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, excess fat triggers the secretion of proinflammatory cytokines, contributing to atherogenesis. Eventually, these factors disrupt blood pressure regulation, potentially leading to elevated blood pressure or hypertension [ 28 , 29 ]. Hence, it is imperative for young individuals to prioritize maintaining a lower BMI to prevent and manage hypertension effectively [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study focused on the triglyceride glucose-body mass index (TyG-BMI), a derivative of body mass index (BMI) and TyG, which can simultaneously capture BMI, blood glucose and lipid profiles, and more closely reflect IR than TyG ( 21 ). Additionally, TyG-BMI has good predictive performance in hypertension, metabolic syndrome, nonalcoholic fatty liver disease, prediabetes, and diabetes ( 22 28 ). Since early-onset T2D is closely associated with IR and obesity, we hypothesized that TyG-BMI may be a useful predictor of early-onset T2D.…”
Section: Introductionmentioning
confidence: 99%